Pengaruh Penambahan Minyak Jelantah dalam Pakan Komersil terhadap Performa Burung Puyuh Jantan Pedaging Coturnix coturnix japonica Fase Akhir (Finisher) - Oktaviana, Dina; Supriadi, Supriadi; Mashur, Mashur (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Increasing the production potential of quail requires better rearing management, especially in the selection of feed ingredients. A feed ingredient that has great potential to be used as a source of energy and fat is used cooking oil. Used cooking oil or waste cooking oil is waste oil that comes from various types of cooking oil, such as corn oil, vegetable oil, ghee, and so on. This oil is used oil for general household use, and can be reused for culinary purposes or even as an alternative feed ingredient for livestock. The aim of this research was to determine the performance of male Coturnix coturnix japonica broiler quail in the final phase (finisher) which received additional feed ingredients in their rations in the form of used cooking oil. This research used 5 different types of feed treatments with 4 repetitions, so that 20 male quail were distributed in 20 experimental unit cages. The five types of treatment are P0 = 98% basal feed, 2% filler, 0% used cooking oil, P1 = 98% basal feed, 1.5% filler, 0.5% used cooking oil, P2 = 98% basal feed, 1% filler , 1% used cooking oil, P3 = 98% basal feed, 0.5% filler, 1.5% used cooking oil, and P4 = 98% basal feed, 0% filler, 2% used cooking oil. The parameters tested in this study were body weight gain, slaughter weight, feed consumption and feed conversion (FCR). All data obtained were analyzed statistically using a complete random design test with a unidirectional pattern, as well as variance ANOVA via SPSS, and if there were differences, they were further tested with the Duncan test. The results of statistical analysis showed that the addition of used cooking oil to commercial feed for male quail had a significant effect on body weight gain and feed consumption P > 0.05, but had no significant effect on slaughter weight and feed conversion value (FCR).